Integrating design thinking into project-based learning with TikTok-mediated activities: A model development study to improve students’ speaking skills - Gotama, Putu Andyka Putra; Putrayasa, Ida Bagus; Sutama, I Made; Sudiana, I Nyoman (Edelweiss Applied Science and Technology, 2026)
Many university students feel anxious about speaking in front of others, struggle to come up with interesting ideas, and find it difficult to organize their thoughts so they can deliver them well. These obstacles highlight the necessity for an instructional methodology that fosters idea generation, organized communication, and genuine speaking practice within a nurturing environment. This study develops and evaluates a teaching model that combines Design Thinking and Project-Based Learning. Additionally, the model is supported by TikTok activities that help students improve their speaking skills. Design Thinking helps students generate creative ideas and frame problems in a structured way. TikTok provides a low-pressure digital space that encourages students to practice speaking in front of others and reduces their anxiety about doing so. Project-Based Learning offers students real-life experiences by having them work together on projects that matter. The study employs a Research and Development methodology following the ADDIE framework. It involves language education and educational technology experts, who confirmed the model. One teacher and 25 college students evaluated the model’s practicality and effectiveness. Data collection was conducted using questionnaires and performance-based speaking tests. The Content Validity Ratio and the Content Validity Index were used to assess content validity. To evaluate effectiveness, the study used a one-group pretest-posttest design and a paired-samples t-test. The findings indicate that the model has high validity, strong practical utility, and significant effectiveness in enhancing speaking skills, as evidenced by a substantial effect size (0.86).